Bioethanol Production from Sugarcane Bagasse and Pineapple Peel Waste and Its Combustion Characteristics - Diswanto Diswanto; Wawan Purwanto; Ahmad Arif; M. Yasep Setiawan; Irma Wirantina Kustanrika (AEEJ : Journal of Automotive Engineering and Vocational Education, 2026)
Growing demand for renewable fuels has increased interest in converting agricultural and fruit-processing residues into bioethanol. This study evaluated sugarcane bagasse and pineapple peel waste as feedstocks for bioethanol production and compared the combustion characteristics of the resulting fuels. Bioethanol was produced through pretreatment, hydrolysis, fermentation using yeast, and distillation. The samples were then examined based on boiling-point range, flame color, flame height, flame area, and flame duration at fuel volumes of 1, 2, and 3 mL. The pineapple peel bioethanol showed a boiling-point range closer to ethanol and produced flame-height values closer to pure ethanol, particularly with 8 g yeast, whereas Pertamax generated the highest flame height and flame area overall. These results indicate that sugarcane bagasse and pineapple peel waste are promising feedstocks for preliminary bioethanol production, with pineapple peel showing better combustion-related characteristics among the waste-derived samples.